Encapsulated Gambir catechin-palm fatty acid distillate as an antibacterial and antioxidant feed additive and its effects on rumen fermentation products - Roni Pazla; Antonius; Novirman Jamarun; Elihasridas; Zaitul Ikhlas; Yelly Fitri; Eni Siti Rohaeni; Usman; Otih Rostiana; Waryat; Setyadjit; Meivie Lintang; et al. (Results in Engineering, 2025)
Catechins are plant-derived polyphenols with strong antibacterial and antioxidant properties. However, their instability and rapid degradation in the rumen limit their effectiveness as functional feed additives in ruminant diets. This study aimed to develop a protective delivery system for gambir-derived catechins using palm fatty acid distillate and calcium oxide (PFAD-CaO) based encapsulation technology and to evaluate its effectiveness in protecting catechins from rumen degradation and enhancing their post-rumen bioactivity. Catechins were extracted from Uncaria gambir using ethyl acetate maceration and tested for antioxidant and antibacterial activities. Encapsulation was performed using PFAD and calcium oxide at varying ratios, and its efficiency was assessed. An in vitro fermentation study was conducted to evaluate nutrient digestibility, rumen fermentation parameters, and catechin bioavailability post-rumen. The optimal extraction condition (1:10 solvent ratio, 24-hour maceration) yielded high catechin content with potent bioactivities. Encapsulation efficiencies ranged from 86.53 % to 91.07 %. Although encapsulation had no significant effect on fermentation characteristics, it improved dry matter digestibility and protected catechins in the rumen, enabling higher availability in the post-rumen. The best formula (3:10 catechin-to-encapsulant ratio at 2 % inclusion) ensured maximum catechin retention and release. PFAD-CaO encapsulation technology is a promising strategy to stabilize and deliver catechins in ruminant diets. This approach offers the potential to enhance animal health through improved antioxidant and antibacterial action beyond the rumen. The findings support the development of PFAD-based encapsulated phytogenic in ruminant nutrition. Future studies should explore in vivo performance, metabolomic responses, and gene expression profiling to confirm the functional benefits of encapsulated catechins.